Estilos de personalidad y de afrontamiento al estrés. - Guato Niama, Gloria Maribel (2025)
Stress is one of the most prevalent issues in today's society, identified as a natural bodily response that manifests in demanding circumstances. To cope with these situations, individuals use different coping styles, which vary according to the context and individual characteristics. This study focused on analyzing personality styles and coping styles in stressful situations using a descriptive bibliographic methodology. A total of 3,960 scientific articles were reviewed from databases such as Web of Science, Scopus, and PubMed. Using the CRF-QS (Critical Review Form – Quantitative Studies) instrument, 19 relevant studies were selected. The results indicate that neuroticism is the least personality style in stressful situations, whereas conscientiousness and openness to experience act as protective factors against stress. Coping styles in stressful situations depend on individual traits and context; however, this research found that the most commonly used coping styles in response to stress were problem-focused coping, emotion-based coping, and avoidance-oriented coping, characterized by distraction or attempts to evade the problem.